Proposed proactive digital forensic approach for cloud computing environment - Samy G.N.; Maarop N.; Wong D.H.; Rahim F.A.; Hassan N.H.; Perumal S.; Magalingam P.; Albakri S.H. (Science Publishing Corporation Inc, 2023)
There are many challenges for the digital forensic process in the cloud computing due to the distinguished features of the cloud computing environment. Many of well-known digital forensic methods and tools are not suitable for cloud computing environment. The multitenancy, multistakeholder, Internet-based, dynamics expendability, and massive data, logs and datasets are examples of the cloud computing environment features that make conducting digital forensics in the cloud computing environment a very difficult task. Therefore, there is a need to develop an appropriate digital forensic approach for cloud computing environment. Thus, this paper proposed a proactive digital forensic approach for cloud computing environment. 2018 Authors.